PEMBUATAN PUPUK UREA LEPAS LAMBAT DENGAN PROSES PELAPISAN UREA ASETALDEHID DAN ZEOLIT - , Moh Eko Subandriyo ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Urea coated with urea-acetaldehyde and zeolite powder was carry out to produce slower release fertilizer, which can increase the effectiveness and efficiency of urea fertilizer used and reduce environmental pollution. The aim of this research was to study urea coating process with urea acetaldehyde and zeolite as slow release fertilizer. Urea was reacted with acetaldehyde at a temperature of Â± 50 Â°C and pH 4 with sulfuric acid catalyst to become urea-acetaldehyde that had lower solubility of the water than that of urea. Urea-acetaldehyde was mixed with zeolite and coated to urea in a rotary drum to form granules. The variables studied were mass ratio of urea with acetaldehyde urea and zeolite powder, and volume ratio of water in coating material. Coated urea products will be analysis as slow release fertilizer (SRF). The results of this study obtained that the molecular weight of urea acetaldehyde is 116.77 g/mol and solubility of urea acetaldehyde is 0.0814 g/mL. Mass transfer coefficient of urea coated fertilizer ( kc ) for variations of mass urea in coated urea ranged between 0.2035 â 0.2210 cm/s, and for variation of the volume of water added in the coating material ranged from 0.163 â 0.2204 cm/s. The average dissolution rate of coated urea in this study is 3 minute 10 second, that rate is still too fast for slow release fertilizer standards but it still lower than that of urea, i.e. 2 minute 45 second. The results of this study show that the mass of urea and the volume of water in the coating material effect on the compressive strength, thickness coatings and dissolution rate of coated urea products. Highest mass fraction of the coating material will make thicker coatings, also greater compressive strength and lower dissolution rate of coated urea products. The greater of volume of water added is, the thicker the coatings, the greater the compressive strength and the lower the dissolution rate of coated urea products are. Keywords : urea, urea acetaldehyde (UA), zeolite, urea coating, fertilizer, slow release fertilizer (SRF), dissolution rate, thickness coatings.